Self-organisation of dodeca-dendronized fullerene into supramolecular discs and helical columns containing a nanowire-like core. Issue 6 (16th April 2015) - Guerra, Sebastiano; Iehl, Julien; Holler, Michel; Peterca, Mihai; Wilson, Daniela A.; Partridge, Benjamin E.; Zhang, Shaodong; Deschenaux, Robert; Nierengarten, Jean-François; Percec, Virgil
Abstract : C60 dendronized with 12 chiral or achiral self-assembling dendrons form discs with C60 at their centre that self-organise into helical columns with a nanowire-like core. Abstract : Twelve chiral and achiral self-assembling dendrons have been grafted onto a [60]fullerene hexa-adduct core by copper-catalyzed alkyne azide "click" cycloaddition. The structure adopted by these compounds was determined by the self-assembling peripheral dendrons. These twelve dendrons mediate the self-organisation of the dendronized [60]fullerene into a disc-shaped structure containing the [60]fullerene in the centre. The fullerene-containing discs self-organise into helical supramolecular columns with a fullerene nanowire-like core, forming a 2D columnar hexagonal periodic array. These unprecedented supramolecular structures and their assemblies are expected to provide new developments in chiral complex molecular systems and their application to organic electronics and solar cells.